Spatial and sectoral distribution of international clusters in the Baltic region - Andrey Mikhaylov; Anna Mikhaylova (European Journal of Scientific Research, 2014)
This article reveals the spatial and sectoral distribution of international clusters in the Baltic macro-region. The research results suggest that there are 28 international clusters in the Baltic region, all of which have an organized structure and are supported by the state. An overwhelming majority of identified clusters represent cross-border type. The most prosperous cross-border regions in this regard are Oresund, Jutland, Bothnian Arc and Oslo - Vaster Gotland (or the GO region). Nearly half of the international clusters studied represent knowledge intensive sectors of economy and almost all are associated with the introduction of innovative solutions. A quarter of all international clusters of the macro-region are engaged in the life science sector, which could be a competitive niche of the Baltic region on the global scale.
Keywords: R11; F23; F63; 330; international cluster; cross-border cluster; transnational cluster; transboundary cluster; Baltic region; Oresund; Regional cluster; Network economics; Business network; Border region